Investigation of the Antibacterial Activity and in vivo Cytotoxicity of Biogenic Silver Nanoparticles as Potent Therapeutics - Hossain, Md. Monir; Polash, Shakil Ahmed; Takikawa, Masato; Shubhra, Razib Datta; Saha, Tanushree; Islam, Zinia; Hossain, Sharif; Hasan, Md. Ashraful; Takeoka, Shinji; Sarker, Satya Ranjan (Frontiers in Bioengineering and Biotechnology, 2019)
Biogenic nanoparticles are the smartest weapons to deal with the multidrug resistant ‘superbugs’ because of their broad spectrum antibacterial propensity as well as excellent biocompatibility. The aqueous biogenic silver nanoparticles (Aq-bAgNPs) and ethanolic biogenic silver nanoparticles (Et-bAgNPs) were synthesized using aqueous and ethanolic extracts of Andrographis paniculata stem, respectively, as reducing agents. Electron microscopic images confirmed the synthesis of almost spherical shaped biogenic silver nanoparticles (bAgNPs). The zeta potentials of the nanoparticles were negative and were -22 and -26 mV for Aq-bAgNPs and Et-bAgNPs, respectively. The antibacterial activity of bAgNPs was investigated against 7 pathogenic (i.e., enteropathogenic Escherichia coli, Salmonella typhi, Staphylococcus aureus, Vibrio cholera, Enterococcus faecalis, Hafnia alvei, Acinetobacter baumannii) and 3 nonpathogenic (i.e., E. coli DH5α, E. coli K12, and Bacillus subtilis) bacteria at different time points (i.e., 12, 16, 20, and 24 h) in a dose-dependent manner (i.e., 20, 40 and 60 μg) through broth dilution assay, disk diffusion assay, CellToxTM Green uptake assay, and trypan blue dye exclusion assay. The lowest minimum inhibitory concentration value for both the bAgNPs was 0.125 μg. Et-bAgNPs showed the highest antibacterial activity against S. aureus at 60 μg after 16 h and the diameter of inhibited zone was 28 mm. The bAgNPs showed excellent hemocompatibility against human as well as rat red blood cells. Furthermore, there was no significant toxicity observed when the level of rat serum ALT, AST, ɤ-GT (i.e., liver function biomarkers) and creatinine (i.e., kidney function biomarker) were determined.